Contraexemplos de Gettier: repensando a justificação epistêmica - Silva, Kariane Marques da (2016)
In the 1960s, a debate has begun in Epistemology about a problem raised by Edmund Gettier in relation to the traditional conception of knowledge. Nowadays the cases presented by Gettier don t seem resolved what makes them even more relevant in current epistemological debates. According to these cases, some scenarios are possible in which necessary and sufficient conditions (belief, truth and justification) are satisfied in order to the traditional definition of knowledge. However, in these cases the subject (a candidate for knowledge) isn t in possession of knowledge. The mainly discussions about it are relative to the concept of epistemic justification, because justification, as an element that identifies the truth of a belief, is supposed not to be sufficient to carry on this function. This insufficiency allows, therefore, the subject be in possession of justification for her/his beliefs and, at the same time, have no knowledge yet. Gettier cases are considered a problem by some theories that defend the standard conditions to the definition of concept of knowledge. Many efforts have been tried to solve these cases with the establishment of an anti-Gettier condition to the definition of knowledge. This way of solution takes to the development of some theories of justification subjected to additional Gettier cases. Unlike this, Laurence Bonjour publishes a critic called The Myth of Knowledge, in which Gettier cases are read like some epistemological pseudoproblems. Bonjour defends that such cases and also the Lottery Paradox are introduced to Epistemology as a result of the adoption of a fallibilist view of knowledge, particularly in relation to the concept of justification. According to him, fallibilists have been failed in their efforts to solve Gettier cases and, hence, they have been complicated the possibility of a coherent concept of knowledge. Furthermore, a mistake in relation to support a fallible justification involves a myth, namely, a worthy philosophical conception of knowledge that can be found in common sense. The fallibilist view, consonant Bonjour, is philosophically unsustainable. His suggestion concerns the abandonment of the myth, because only with this way epistemological pseudoproblems would be dissolved, like those problems set by Gettier counterexamples.